2020
DOI: 10.1163/22941932-bja10029
|View full text |Cite
|
Sign up to set email alerts
|

Computer-assisted timber identification based on features extracted from microscopic wood sections

Abstract: Wood anatomy is one of the most important methods for timber identification. However, training wood anatomy experts is time-consuming, while at the same time the number of senior wood anatomists with broad taxonomic expertise is declining. Therefore, we want to explore how a more automated, computer-assisted approach can support accurate wood identification based on microscopic wood anatomy. For our exploratory research, we used an available image dataset that has been applied in several computer vision studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 48 publications
1
28
0
Order By: Relevance
“…(2020) provide a table of the proportion of the 7,371 anatomical descriptions in InsideWood with each anatomical character, and this gives a good indication of which ones have particular diagnostic value singly and in combination. As with macroscopy, expertise is necessary, and machine learning and other neural network methods are being investigated to aid or reduce the need for human expertise in order to improve point‐of‐contact identification of suspect wood (e.g., Lens et al., 2020; Martins et al., 2013; Silva et al., 2017). These developments do not eliminate the need for expert wood anatomists but provide alternative methods of identification in the current reality of the declining population of expert anatomists despite the increased global trade in wood products.…”
Section: Methods Used For Identificationmentioning
confidence: 99%
“…(2020) provide a table of the proportion of the 7,371 anatomical descriptions in InsideWood with each anatomical character, and this gives a good indication of which ones have particular diagnostic value singly and in combination. As with macroscopy, expertise is necessary, and machine learning and other neural network methods are being investigated to aid or reduce the need for human expertise in order to improve point‐of‐contact identification of suspect wood (e.g., Lens et al., 2020; Martins et al., 2013; Silva et al., 2017). These developments do not eliminate the need for expert wood anatomists but provide alternative methods of identification in the current reality of the declining population of expert anatomists despite the increased global trade in wood products.…”
Section: Methods Used For Identificationmentioning
confidence: 99%
“…In a comparative study of DL and conventional ML models [ 55 ], CNN-based models, Inception-v3 [ 165 ], SqueezeNet [ 164 ], ResNet [ 25 ], and DenseNet [ 166 ], all models achieved better performance than k-NN models trained with LBP or LPQ features. Lens et al [ 72 ] also reported that VGG16 and ResNet101 models had better classification performance for the UFPR dataset than those trained with texture features. The CNN with residual connections proposed by Fabijańska et al [ 65 ] identified 14 European trees better than other popular CNN architectures.…”
Section: Deep Learningmentioning
confidence: 99%
“…All wood image types can be used as data for identification. The most commonly used image types are macroscopic images [50,54,[62][63][64][65], X-ray computed tomographic (CT) images [66,67], stereograms [20,21,26,68,69], and micrographs [47,[70][71][72] (Fig. 2a).…”
Section: Image Typementioning
confidence: 99%
See 2 more Smart Citations